CRISPR-Cas9-AAV versus lentivector transduction for genome modification of X-linked severe combined immunodeficiency hematopoietic stem cells - Brault, Julie; Liu, Taylor; Liu, Siyuan; Lawson, Amanda; Choi, Uimook; Kozhushko, Nikita; Bzhilyanskaya, Vera; Pavel-Dinu, Mara; Meis, Ronald J.; Eckhaus, Michael A.; Burkett, Sandra S.; Bosticardo, Marita; et al. (Frontiers in Immunology, 2023)
Ex vivo gene therapy for treatment of Primary Immune Deficiency (PID) diseases have demonstrated significant clinical benefit in multiple Phase I/II clinical trials. Current approaches rely on engineered retroviral vectors to randomly integrate copy(s) of gene-of-interest in autologous hematopoietic stem/progenitor cells (HSPCs) genome permanently to provide gene function in transduced HSPCs and their progenies. To circumvent concerns related to potential genotoxicities due to the random vector integrations in HSPCs, targeted correction with CRISPR-Cas9-based genome editing offers improved precision for functional correction of multiple PID. We compare the two approaches for integration of IL2RG transgene for functional correction of HSPCs from patients with X-linked Severe Combined Immunodeficiency (SCID-X1); delivery via current clinical lentivector (LV)-IL2RG versus targeted insertion (TI) of IL2RG via homology-directed repair (HDR) when using an adeno-associated virus (AAV)-IL2RG donor following double-strand DNA break at the endogenous IL2RG locus. In vitro differentiation of LV- or TI-treated SCID-X1 HSPCs similarly overcome differentiation block into Pre-T-I and Pre-T-II lymphocytes but we observed significantly superior development of NK cells when corrected by TI (40.7% versus 4.1%, p = 0.0099). Transplants into immunodeficient mice demonstrated robust engraftment (8.1% and 23.3% in bone marrow) for LV- and TI-SCID-X1 HSPCs with superior T cell development (88.5%) following TI-IL2RG compared to LV (53.2%, p <0.0001). Extensive specificity analysis of CRISPR-Cas9 editing with rhAmpSeq covering 82 predicted off-target sites found no evidence of indels in edited cells before (in vitro) or following transplant, in stark contrast to LV’s non-targeted vector integration sites. Together, the improved efficiency and safety of IL2RG correction via CRISPR-Cas9-based TI over LV approaches provides a strong rationale for a clinical trial for treatment of SCID-X1 patients.